Fault Lines : How Hidden Fractures Still Threaten the World Economy - Rajan, Raghuram (Book collections on Project MUSE., 2010)
Raghuram Rajan was one of the few economists who warned of the global financial crisis before it hit. Rajan shows how the individual choices that collectively brought about the economic meltdown--made by bankers, government officials, and ordinary homeowners--were rational responses to a flawed global financial order in which the incentives to take on risk are incredibly out of step with the dangers those risks pose. He traces the deepening fault lines in a world overly dependent on the indebted American consumer to power global economic growth and stave off global downturns. He exposes a system where America's growing inequality and thin social safety net create tremendous political pressure to encourage easy credit and keep job creation robust, no matter what the consequences to the economy's long-term health; and where the U.S. financial sector, with its skewed incentives, is the critical but unstable link between an overstimulated America and an underconsuming world.